PUBLIC ADMINISTRATION AND SOCIAL POLICY IN PALESTINE: CASE STUDY OF UNEMPLOYMENT IN GAZA STRIP AND WEST BANK - Hajjaj, Ola (Univerzita Pardubice, 2016)
This study aims to highlight the State and Public Administration policies on social problems and unemployment in relation to unemployment problem and employment policies in Palestine. It analyses the different trends of unemployment in West Bank and Gaza Strip as Palestine is fragmented geographically. Some of the regional unemployment characteristics are targeted in order to demonstrate effects of public administration measures and show the differences of unemployment rates between the two mentioned areas and its reasons. Comparison depending on the regional distribution is done to discuss the population density and political stability in both of them. The study has proved that Public Administration realised by Palestinian National Authorities has been effective in West Bank, whereas in Gaza Strip the unemployment rates shows continuous increment. Because of the current political situation in Palestine, Gaza Strip is no longer under the administration of the Palestinian National Authority as a result of internal Palestinian conflict.
Veřejná správa a sociální politika v Palestině: Případová studie nezaměstnanosti v pásmu Gazy a na Západním břehu
Keywords: Unemployment; Employment; Gaza Strip; West Bank; Labour market; Policy